Assembly of zein/propylene glycol alginate nanoparticles in aqueous ethanol and the binding kinetics. (May 2023) - Yu, Yang; Li, Shi-Yu; Xu, Tong-Cheng; Huang, Guo-Qing; Xiao, Jun-Xia
Abstract: The interaction between zein and propylene glycol alginate (PGA) in aqueous ethanol was investigated to fabricate novel zein-based nanoparticles. The results indicated that electrostatic attraction could occur between the two polyelectrolytes in aqueous ethanol. The interaction was insensitive to temperature variation but was weakened in high total biopolymer concentrations, and the optimum conditions were pH 5.0, zein to PGA mass ratio 2:1, total solid concentration 0.2% (w/v), and ethanol concentration 70% (v/v) in the absence of salts, which could yield positively charged zein/PGA nanoparticles of 120 nm according to atomic microscope observation. Isothermal titration calorimetry, quartz crystal microbalance analysis, and microscale thermophoresis revealed that zein exhibited much lower stoichiometry but greatly higher affinity in binding PGA than in the zein/PGA nanoparticles prepared by the conventional anti-solvent and pH cycling methods. Hence, the self-assembly in 70% ethanol was a feasible way to fabricate novel zein/PGA nanoparticles with homogeneous structure and enhanced stability in a single step. Graphical abstract: Image 1 Highlights: Electrostatic interaction dominates in zein/PGA interaction in 70% aqueous ethanol. Assembly in 70% ethanol yields smaller zein/PGA NPs than traditional methods. Assembly in 70% ethanol confers lower stoichiometry than traditional methods. Assembly in 70% ethanol yields higher affinity than traditional methods.